Different fat-to-fiber ratios by changing wheat inclusion level impact energy metabolism and microbial structure of broilers - Jiang, Qiuyu; Zhao, Lihua; Ban, Zhibin; Zhang, Bingkun (Frontiers in Microbiology, 2024)
Herein, this study aimed to explore the effects of fat-to-fiber ratios on nutrient transporter, energy metabolism and gut microbiota when ingredients composition was altered. A total of 240 as-hatched broiler chickens were randomly assigned into three groups including low fat-high dietary fiber (LF-HD), medium fat-medium dietary fiber (MF-MD) and high fat-low dietary fiber (HF-LD), with diets being iso-protein, and broilers were offered the same commercial diets from 21 to 42 d. The data were analyzed using one-way ANOVA of SPSS. Results showed that HF-LD diet significantly increased glucose content and decreased triglyceride in serum of broilers (P < 0.05). The mRNA abundance of jejunal gene involved in glucose transporter and tricarboxylic acid (TCA) cycle was significantly increased in broilers fed with HF-LD diets. Compared with LF-HD, HF-LD had a lower abundance of Anaerofilum and CHKCI001, and an increased proportion of beneficial bacteria such as Alistipes, Catenibacillus, Intestinimonas, Lactobacillus and Peptococcus (P < 0.05). Functional prediction of these microbial changes indicated that HF-LD diet drove caecal microbiota to participate in carbohydrate metabolism and TCA cycle (P < 0.05). Dietary HF-LD-induced microbiota changes were positively correlated with growth performance of broilers (P < 0.05). In conclusion, HF-LD diet increased glucose transporters and energy metabolism in intestine and shaped microbial structure and metabolic pathways, which may benefit the growth performance of broilers.